Severe left ventricular systolic dysfunction is independently associated with high on-clopidogrel platelet reactivity - Motovska, Zuzana; Ondrakova, Martina; Doktorova, Magdalena; Widimsky, Petr (American journal of cardiovascular drugs, 2014)
OBJECTIVE: The purpose of the present study was to investigate the association between left ventricular systolic function and the response to clopidogrel. METHODS: The efficacy of clopidogrel was measured by the vasodilator-stimulated phosphoprotein phosphorylation 20 ± 4 h after 600 mg of clopidogrel. High on-clopidogrel platelet reactivity (HCPR) was defined as a platelet reactivity index (PRI) ≥50%. The 30-day combined incidence of death, non-fatal acute coronary syndrome, re-percutaneous coronary intervention (PCI), stent thrombosis, and stroke was also investigated. RESULTS: The study group consisted of 519 patients undergoing PCI. The values (mean and 95% confidence interval) of the PRI were as follows: 40.4% (37.8-43.0) in patients with left ventricular ejection fraction (LVEF) >50%, 42.4% (39.3-45.6) in patients with LVEF 35-50%, and 46.7% (40.6-52.9) in patients with LVEF <35% (p = 0.013). The proportions of patients with HCPR were 35.9% in patients with LVEF ≥35 and 51.9% in patients with LVEF <35% (p = 0.022). After adjustment for variables that significantly influenced clopidogrel efficacy, LVEF <35% was found to be independently associated with HCPR (p = 0.039). The 30-day combined clinical endpoint occurred in 18% of patients with LVEF <35% and in 7.3% of patients with LVEF ≥35% (p = 0.026). The 30-day incidence of all-cause mortality was 14% in patients with LVEF <35 and 1.0% in patients with LVEF ≥35% (p < 0.001). CONCLUSION: An LVEF <35% was found to be independently associated with HCPR.
Keywords: tepový objem; stenty; Humans; Ticlopidine; fosfoproteiny; tiklopidin; Stroke Volume; lidé středního věku; koronární angioplastika; klopidogrel; Stroke; Female; Aged; trombocyty; mikrofilamentové proteiny; inhibitory agregace trombocytů; senioři; lidé; Acute Coronary Syndrome; Cell Adhesion Molecules; cévní mozková příhoda; Stents; Blood Platelets; ženské pohlaví; Male; Vasodilator-Stimulated Phosphoprotein; Middle Aged; Retrospective Studies; molekuly buněčné adheze; dysfunkce levé srdeční komory; Microfilament Proteins; Ventricular Dysfunction, Left; Percutaneous Coronary Intervention; retrospektivní studie; Clopidogrel; akutní koronární syndrom; mužské pohlaví; Platelet Aggregation Inhibitors; Phosphoproteins; fosfoprotein stimulovaný vazodilatátorem